Segmentasi, Targeting, dan Positioning terhadap Keputusan Pembelian di Era Digital: Peran Motivasi Konsumen - Resti Yulistria; Vanessa Gaffar; Hilda Monoarfa; Ade Sobandi (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2026)
Purpose – This study aims to analyze the effect of segmenting, targeting, and positioning on consumer purchase decisions in the digital era, both partially and simultaneously, and to examine the role of consumer motivation as a moderator of that relationship.Methodology – This research adopts a quantitative approach to objectively measure the relationships among variables using numerical data. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM), as the constructs of segmentation, targeting, positioning, consumer motivation, and purchase decisions are latent variables and involve moderation effects. Data were collected through an online structured questionnaire survey of 200 consumers who had previously made purchases via digital platforms. Purposive sampling was employed to ensure that respondents had relevant experience with digital marketing activities.Originality/Novelty – The originality of this study lies in its integration of the classical segmenting, targeting, and positioning framework with contemporary digital consumer behavior, particularly by positioning consumer motivation as a moderating variable that deepens the understanding of this relationship.Implications – The findings show that segmentation, targeting, and positioning each have a positive and significant effect on consumer purchase decisions, both partially and simultaneously, and that consumer motivation strengthens the effect of segmentation on purchase decisions. This study provides both theoretical insights and practical implications for the development of more adaptive, consumer-oriented digital marketing strategies.